A study on the child beggar syndicates in Malaysia and Singapore. / Norhafizan Mat Yasin, Saidatul Salwa Abdul Razak and Hani Nurzafirah Badarludin - Mat Yasin, Norhafizan; Abdul Razak, Saidatul Salwa; Badarludin, Hani Nurzafirah (2010)
This research study comprises the points relating to child protection in terms of child beggar, in particular. The issue would be the adequacy of the current law in developing the advancement in the protection of the children together with the enforcement of the law by the government agency and non governmental organization, its workability towards the people and the current situation as a whole. The comparison would be with The Republic of Singapore regarding the laws and relevant authorities which responsible and correlated with the child protection, specifically, child beggar. It is for the reason that the Republic of Singapore appears to be a country with a lesser number of child beggar or 'street kids' compared to Malaysia. The method used in this research to obtain the information or the relevant data would be mainly by the way of library research and internet research. The semi-structured interview will be as an endorsement if more information needs to be attained. In completing this research, the scope of the study will be focusing on the laws and the effort made by the authorities and relevant agencies in both Malaysia and Singapore for the purpose of protecting the child beggar and the protection of the children from begging. In the surface, Singapore provides a small and rare cases pertaining to child beggar or 'street kids' as compared to Malaysia, the child beggar is everywhere. There is need to call out for the advancement of the law relating to child protection to decrease the number of child beggar which will affect the society as a whole. The cooperation from the public at large to provide a better environment for the well being of the children needs to be taken into consideration as the children are the backbones of a nation.